PENINGKATAN KETERAMPILAN MENULIS TEGAK BERSAMBUNG MELALUI METODE GUIDED WRITING PADA PESERTA DIDIK KELAS III SDN 07 TALAMAU - Umil Azmah, Arhaya; Azmi Alwi, Nur; Ari Suriani; Muhammadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the results of field observations, namely the still low cursive writing skills of grade IIIA students at SDN 07 Talamau. These problems are shown by students in understanding the direction and sequence of cursive strokes, letter shapes that do not conform to the rules of cursive, non-uniform letter sizes and inconsistent letter spacing. In addition, the writing learning process is still centered on the teacher so that students still do not play an active role in the learning process. This study aims to describe the improvement of students' cursive writing skills through the guided writing method. The type of research used is Classroom Action Research (CAR) using qualitative and quantitative approaches. This study was carried out in two cycles, with research procedures consisting of planning, implementation, observation, and reflection stages. The research data obtained are related to cursive writing skills through the guided writing method. Data collection techniques include observation analysis, tests and non-tests. The subjects of this study were the class teacher as observer, the researcher as practitioner, and 14 grade IIIA students of SDN 07 Talamau. The results of the study showed an improvement in students' cursive writing skills. The average cursive writing skill in cycle I was 73.85%, which then increased to 84.27% in cycle II. Therefore, it can be concluded that the guided writing method can improve students' cursive writing skills in Indonesian language learning in third grade at SDN 07 Talamau. Keywords: Writing Skills, Cursive Writing, Guided Writing Method.